Mechanical understanding of hunting waves generated by killer whales. Issue 4 (8th April 2019) - You, Hojung; Hwang, Jin Hwan; Park, Yong Sung
Abstract: The wave wash hunting employed by Orcinus orca, also known as killer whales, is unique in that the prey is hunted outside of the water by generating waves. To quantitatively analyze the specific mechanism of the wave wash, data were obtained using computational fluid dynamics (CFD), and wave theory was introduced as the theoretical background to clarify the mechanism. The relationships between the swimming characteristics and wave parameters are defined in this paper. The results obtained by numerical investigation revealed that the wavelength increased with the swimming speed. Additionally, the wave height increased as the swimming speed increased and the swimming depth became shallower, and subsequently converged to a maximum of 2.42 m. The success of hunting is determined by two wave parameters, which indicate the intensity of the wave wash: the wave height and force exerted on the prey. The metabolic rate and the drag force are considered to evaluate the efficiency of the locomotion, which varied according to the swimming speed ( V ) and swimming depth ( d ) of the whales. To generate hunting waves efficiently, the optimal ranges of V and d were estimated to be 3 ~ 5 m/s and 0.5 m ~ 1.1 m respectively.